Alternative Splicing Regulator RBM20 and Cardiomyopathy - Watanabe, Takeshi; Kimura, Akinori; Kuroyanagi, Hidehito (Frontiers in Molecular Biosciences, 2018)
RBM20 is a vertebrate-specific RNA-binding protein with two zinc finger (ZnF) domains, one RNA-recognition motif (RRM)-type RNA-binding domain and an arginine/serine (RS)-rich region. RBM20 has initially been identified as one of dilated cardiomyopathy (DCM)-linked genes. RBM20 is a regulator of heart-specific alternative splicing and Rbm20ΔRRM mice lacking the RRM domain are defective in the splicing regulation. The Rbm20ΔRRM mice, however, do not exhibit a characteristic DCM-like phenotype such as dilatation of left ventricles or systolic dysfunction. Considering that most of the RBM20 mutations identified in familial DCM cases were heterozygous missense mutations in an arginine-serine-arginine-serine-proline (RSRSP) stretch whose phosphorylation is crucial for nuclear localization of RBM20, characterization of a knock-in animal model is awaited. One of the major targets for RBM20 is the TTN gene, which is comprised of the largest number of exons in mammals. Alternative splicing of the TTN gene is exceptionally complicated and RBM20 represses >160 of its consecutive exons, yet detailed mechanisms for such extraordinary regulation are to be elucidated. The TTN gene encodes the largest known protein titin, a multi-functional sarcomeric structural protein specific to striated muscles. As titin is the most important factor for passive tension of cardiomyocytes, extensive heart-specific and developmentally regulated alternative splicing of the TTN pre-mRNA by RBM20 plays a critical role in passive stiffness and diastolic function of the heart. In disease models with diastolic dysfunctions, the phenotypes were rescued by increasing titin compliance through manipulation of the Ttn pre-mRNA splicing, raising RBM20 as a potential therapeutic target.